\(\frac{4}{5}-2x=\frac{2}{5}+3x\)
\(\frac{4}{5}-\frac{2}{5}=2x+3x\)
\(\frac{2}{5}=5x\)
\(x=\frac{2}{25}\)
Ta có :\(\frac{4}{5}-2x=\frac{2}{5}+3x\)
\(\Leftrightarrow\) \(\frac{4}{5}-\frac{2}{5}=3.x+2.x\)
\(\Leftrightarrow\)\(\frac{2}{5}=5.x\)
\(\Leftrightarrow x=\frac{2}{5}:5\)
\(\Leftrightarrow x=\frac{2}{25}\)
~~~ AI NGANG QUA CHO CHÁU XIN 1 L~I~K~E~~~
Ta có:
\(\frac{4}{5}-2x=\frac{2}{5}+3x\)
=>\(\frac{4}{5}-2x-\frac{2}{5}=3x\)
=>\(\frac{2}{5}-2x=3x\)
=>\(\frac{2}{5}=3x+2x\)
=>\(\frac{2}{5}=5x\)
=>\(x=\frac{2}{5}:5\)
=>\(x=\frac{2}{25}\)
Vậy \(x=\frac{2}{25}\)